The Role of Central Bank Monetary Policy in Controlling Inflation and Exchange Rates - Jajang Herawan; Yadi Janwari; Sofyan Al-Hakim (al-Afkar, Journal For Islamic Studies, 2024)
This research explains the role of the central bank as a monetary policy regulator that has the ability to control inflation and the exchange rate. This is proven by the circulation of currency in the economy which reflects changes in the amount of currency in circulation, interest rates, credit, exchange rates, and many other economic and financial variables. The method used in this article uses a qualitative descriptive approach. Descriptive refers to the researcher's efforts to systematically and accurately describe those who study or criticize literature, whether from books, journals or other documents, based on several opinions based on a number of research results from journalists or document critics. The results of the review show that a significant difference in Islamic monetary policy is that Islamic economics does not provide guarantees regarding nominal values, profit margins, or interest rates. Therefore, monetary policy automatically becomes sharia monetary policy, that is, it does not use interest rates as its operational target. The tool used is sharia law.